2021
DOI: 10.1002/joc.7257
|View full text |Cite
|
Sign up to set email alerts
|

Overall uncertainty of climate change impacts on watershed hydrology in China

Abstract: The hydrological projections provided by the outputs of Global Climate Models (GCMs) combining hydrological models include multi-source uncertainties, which may challenge the formulation of relevant adaption and mitigation policies. In this paper, the overall uncertainty and the relative contribution of each uncertainty component were investigated for hydrological projections over 408 watersheds in China by using 3 shared socioeconomic pathway emission scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5), 21 GCMs, 8 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 72 publications
(100 reference statements)
0
9
0
Order By: Relevance
“…Uncertainties in the precipitation data of the GCMs are widely reported [5,11,[41][42][43]. Large uncertainties existed in precipitation data even after using the bias correction methods.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainties in the precipitation data of the GCMs are widely reported [5,11,[41][42][43]. Large uncertainties existed in precipitation data even after using the bias correction methods.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated these uncertainties on watershed hydrology [18,35,36]. Zhang et al [37] investigated the overall uncertainty and the relative contribution of each uncertainty component for hydrological simulations over 408 watersheds in China by using 3 emission scenarios, 21 GCMs, 8 downscaling methods, 4 hydrological models, and 2 sets of optimized hydrological model parameters. They found that the uncertainty related to GCMs contributes most with the percentage of 60%, followed by the uncertainty related to hydrological models (approximately 7%) and downscaling methods (less than 1%).…”
Section: Discussionmentioning
confidence: 99%
“…To better understand both simulated and observed ICV in different regions, it is necessary to divide the whole Chinese territory into subregions. This study used seven subregions: northeast China (NE), north China (N), east China (E), south China (S), northwest China (NW), southwest China (SW) and Qinghai-Tibet Plateau (QT), as shown in Figure 1 (Wang & Li, 2007;Zhang et al, 2021). Regional average values in this study are described by spatially averaging the values of grids within the same region with latitudinal weight.…”
Section: Study Areamentioning
confidence: 99%